PEMODELAN REGRESI COX DAN REGRESI WEIBULL WAKTU SEMBUH DIARE PADA BALITA - Siti Alfiatur Rohmaniah; Danardono Danardono (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2016)
There are some consequences that occur because of diarrhea such as low levels of hemoglobin, weight loss, and dehydration. Severe dehydration can lead to death. This study aims to model the time cured of diarrhea on infants used the Cox regression method and Weibull regression to determine the factors that signicantly influence the long diarrhea. The method used to analyze data on infants under diarrhea includes sex, duration of diarrhea from beginning to heal, age of the children, the value of nutrition in infants and toddlers hemoglobin levels. Further, it continued by modeling these factors using cox regression and regression weibull. The results obtained the nutritional value on infants signicantly eect on diarrhea in infants.